Fracture healing in a collagen‐induced arthritis rat model: Radiology and histology evidence. Issue 11 (13th July 2018) - Hu, Yiping; Zhang, Tiantian; Huang, Huan; Cheng, Wenxiang; Lai, Yuxiao; Bai, Xueling; Chen, Jianhai; Yue, Ye; Zheng, Zhengtan; Guo, Chengshan; Qin, Ling; Zhang, Peng
ABSTRACT: This research was designed to investigate the fracture healing pattern in a rheumatoid arthritis (RA) rat model. A mid‐shaft femur fracture (RA + F) model and normal fracture (NF) model as control were established. Micro‐CT, H&E staining, TB staining, SO staining, tartrate‐resistant acid phosphates, and immunohistochemistry test were performed. In the micro‐CT images and H&E stains, fracture gaps were evident in the RA + F group 4 and 8 weeks after fracture. In detail, the bone mineral density, the ratio of bone volume to tissue volume, and trabecular thickness of the RA + F group were significantly lower than those of the NF group at all time points. Trabecular number value was significantly lower in the RA + F group 4 weeks after surgery in comparison with that of the NF group. Furthermore, the structure model index test result of the RA + F group was significantly higher than that of the NF group at all time points. TB staining and SO staining test results showed that the NF group had more cartilaginous callus in the earlier stage of bone healing process (4 weeks), and less cartilage callus formation in the later stage (8 weeks) in comparison with that of the RA + F group. Osteoclasts statistics score in the NF group were obviously lower than that of the RA + F group at all time points. MMP‐3 and OPN protein levels of the fracture area in the RA + F group were significantly higher than those in the NF group. This study improves the understanding of the bone healing characteristics in patients with RA. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2876–2885, 2018.